2019
DOI: 10.1126/science.aay8746
|View full text |Cite
|
Sign up to set email alerts
|

Median raphe controls acquisition of negative experience in the mouse

Abstract: Adverse events need to be quickly evaluated and memorized, yet how these processes are coordinated is poorly understood. We discovered a large population of excitatory neurons in mouse median raphe region (MRR) expressing vesicular glutamate transporter 2 (vGluT2) that received inputs from several negative experience–related brain centers, projected to the main aversion centers, and activated the septohippocampal system pivotal for learning of adverse events. These neurons were selectively activated by aversiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(79 citation statements)
references
References 78 publications
(163 reference statements)
3
72
1
Order By: Relevance
“…However, there were no projections from DR glutamatergic and GABAergic neurons and scarce projections from MR GABAergic neurons to the LH, only MR glutamatergic neurons sent strong projections to the LH (mainly assembled in the medial part of LH) ( Figure 4B (Szőnyi et al, 2019), which supported the reliability of this projection pattern. The specific reciprocal connections between MR glutamatergic neurons and the LH suggested that MR glutamatergic neurons might be involved in some specific functions related to the LH.…”
Section: Habenula-raphe Circuitsmentioning
confidence: 52%
See 3 more Smart Citations
“…However, there were no projections from DR glutamatergic and GABAergic neurons and scarce projections from MR GABAergic neurons to the LH, only MR glutamatergic neurons sent strong projections to the LH (mainly assembled in the medial part of LH) ( Figure 4B (Szőnyi et al, 2019), which supported the reliability of this projection pattern. The specific reciprocal connections between MR glutamatergic neurons and the LH suggested that MR glutamatergic neurons might be involved in some specific functions related to the LH.…”
Section: Habenula-raphe Circuitsmentioning
confidence: 52%
“…The dorsal raphe nucleus (DR) and median raphe nucleus (MR) are important modulatory centers involved in a multitude of functions (Domonkos et al,2016;Huang et al, 2019;Szőnyi et al, 2019). They are implicated to have different and even antagonistic roles in the regulation of specific functions, such as emotional behavior, social behavior and aggression (Balázsfi et al, 2018;Ohmura et al, 2020;Teissier et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In vertebrates, for instance, visual information is extensively processed in the retina, thalamus, parts of the cerebrum, and optic tectum; and in arthropods in the retina, lamina, medulla, lobula and central complex of the brain (Strausfeld, 2012;Feinberg and Mallatt, 2016a). As another illustration of extreme regional specialization, the core of the vertebrate brain has elaborated a dizzying number of centers for affective (emotional) consciousness: the habenula, basal forebrain, periaqueductal gray, parts of the reticular formation and more (Figure 3; Berridge and Kringelbach, 2015;Feinberg and Mallatt, 2016a;Hu, 2016;Feinberg and Mallatt, 2018a;Siciliano et al, 2019;Szõnyi et al, 2019).…”
Section: The Special Features Are Emergent Featuresmentioning
confidence: 99%